Perception of pharmacists regarding over-the-counter medication: A survey - Ravichandran, Abinaya (Indian J Pharmacol, 2016)
OBJECTIVE: To assess knowledge, attitude, and practice of the pharmacists toward dispensing the over-the-counter (OTC) medications using questionnaire. MATERIALS AND METHODS: cross-sectional questionnaire-based study was conducted to assess the knowledge, attitude, and practice among pharmacists regarding OTC medications. Eighty out of hundred filled questionnaires were received from various pharmacists from medical shops in and around Kolar. Data were analyzed using descriptive statistics. RESULTS: A total of 74.6% responded to the questionnaire. Most of the dispensers (97.3%) at pharmacy were qualified with a D.Pharma/B.Pharma degree. Pharmacists with B.Pharma (80%) were able to define OTC. Majority of them had more than ten consumers taking OTC per week. Among the OTCs dispensed, common were analgesics (75%), antacids (48%), antihistaminics (40%), and others (35%). The choice of OTC brand was made by pharmacists (58.7%) and consumers (41.2%). Most of them (96.5%) asked the consumer's complaints before dispensing the drug, but only few (51%) counseled them regarding the instructions to administer medication. The brand of OTC was influenced by prescriptions of local doctor (60%), consumer's choice (31.2%), cost of the drug (16.7%), and medical representatives (5%). OTCs were safe to dispense, according to 90% of the pharmacists; however, among them, 50% expressed that the consumers should first consult doctor. CONCLUSION: Majority of the pharmacists were qualified to dispense medication, but only few knew about OTC drugs. Analgesics were most commonly used OTC. These drugs were safe to dispense, however, consulting doctor before taking medications was suggested by some of them.